Environmental risk assessment of pyrometallurgical residues derived from electroplating and pickling sludges. (10th March 2018) - Zhou, Cailing; Ge, Shifu; Yu, Hui; Zhang, Tianqi; Cheng, Hailei; Sun, Qi; Xiao, Rui
Abstract: Pyrometallurgical residues from disposing of electroplating and pickling sludge (REPS), including copper (Cu) sludge (RCS), are often recycled as building materials in China. Although it is of great importance to assess the environmental risk of pyrometallurgical residues, few studies have been performed. In this study, REPS and RCS were analyzed from the aspects of metal speciation, concentration, leaching toxicity, and risk assessment ( I geo, PER, RSP, and SQGs ), respectively. Results of metal concentrations showed that the sintered block and incinerated residue contained more potentially toxic metals (PTM) than the remainder of the slag. A significance analysis suggested that the Cu concentration in the pyrometallurgical residues was closely related to both the sludge type and its process, and the concentrations of chromium (Cr) and nickel (Ni) were mainly related to the disposal process, while the concentrations of other PTM were not correlated with sludge type or the process. Leaching toxicity analyses indicated that the incineration residues were hazardous wastes according to the Chinese standard and building materials made from such residues would be unqualified for extreme environments. Moreover, speciation and correlation analyses revealed that only speciation of Cu and cadmium (Cd) was strongly negatively correlated with leaching toxicity, and residual speciation was not the only factor determining metal stability. Thus, a new relative comprehensive assessment value ( F ), as a combination of metal concentration and speciation, was introduced to evaluate environmental risk of pyrometallurgical residues, which was more reliable than the results of existing assessments ( I geo, PER, RSP, and SQGs ). Such an index indicates that the pyrometallurgical residues derived from incineration and sintering disposal processes presented the highest risk. Graphical abstract: Highlights: Correlation analysis was taken to explore the relationships among speciation, concentration and leaching toxicity. Building materials of the pyrometallurgical residues were unqualified under extreme environment. A new relative integrated assessment value ( F ) was developed combined with the existing assessment methods.